Correlation of Width of Attached Gingiva on Oral Hygiene Maintenance and Gingival Health - Pradhan, Shaili; Shrestha, Benju (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: Attached gingiva aids in increased resistance to external injury and contribute in stabilisation of gingival margin against frictional forces as well as dissipates physiological forces exerted by the muscular fibers of the alveolar mucosa on gingival tissues. Objective: To assess width of attached gingiva in adults and correlate with oral hygiene maintenance and gingival inflammation. Methods: A cross-sectional study was conducted in patients aged 20-40 years visiting dental OPD with healthy periodontium. Plaque index (PI) and Gingival index (GI) were recorded. Mucogingival junction was determined by visual and functional method. Keratinised gingiva width (KGW) and probing pocket depth (PPD) was recorded and attached gingiva width (AGW) was calculated as (KGW–PPD). Results: Total 85 patients (43 males and 42 females) enrolled in this study. Among total, 48.23% had AGW<1 mm. AGW <1 mm most commonly was found in mandibular first premolar, highest mean AGW was found in maxillary incisors. The mean GI and PI values for AGW<1 mm were found to be higher than those for AGW≥ 1 mm. However, result did not show any significant relation between AGW and severity of gingival inflammation (P value 0.608) and plaque control (P value 0.297). Conclusion: The correlation between attached gingiva width and severity of gingival inflammation and plaque index was not significant statistically. However, the mean gingival index and plaque index score were higher for the attached gingiva width less than 1 mm.